Ethical dimension in dentistry practice. Personalist viewpoint - Izzeddin Abou, Roba; Spina, María; Tosta, Egilda (Acta Bioethica, 2010)
In the practice of dentistry, professionals face diverse ethical dilemmas permanently. Every dentist must make determinations whether he/she has competence for a particular diagnose or to carry out specific treatments in specific clinical circumstances. Issues such as these have given place to increasing discussions and debates with respect to health care ethics. Ethical worries are specially relevant in dentistry field, since while number of studies increase in this field, the limit separating practice from obtaining information for research purposes is narrowed.